2020
DOI: 10.1172/jci137530
|View full text |Cite
|
Sign up to set email alerts
|

The DEL-1/β3 integrin axis promotes regulatory T cell responses during inflammation resolution

Abstract: like domains-3). The second EGF-like repeat (E2) contains an RGD (Arg-Gly-Asp) motif, which enables DEL-1 to bind αvβ3 integrin (19, 26), whereas its discoidin-I-like domains can bind the "eat-me" signal phosphatidylserine on apoptotic cells (22, 27). These interactions allow DEL-1 to serve as a molecular bridge DEL-1 is a locally secreted 52-kDa protein that interacts with distinct integrins and homeostatically regulates the initiation and resolution of inflammation (18-25). DEL-1 consists of 3 N-terminal EGF… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
27
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 34 publications
(28 citation statements)
references
References 87 publications
1
27
0
Order By: Relevance
“…Specifically, factors regulating peripheral inflammation may in fact do so by additionally modulating central inflammatory processes. For instance, the homeostatic protein developmental endothelial locus 1 (DEL1; also known as EGF-like repeat and discoidin I-like domain-containing protein 3), which was shown to inhibit initiation of periodontal inflammation and to promote its resolution [144][145][146][147] , may also regulate central inflammatory processes via its function to modulate demand-adapted myelopoiesis in the bone marrow 148 .…”
Section: Wwwnaturecom/nrimentioning
confidence: 99%
“…Specifically, factors regulating peripheral inflammation may in fact do so by additionally modulating central inflammatory processes. For instance, the homeostatic protein developmental endothelial locus 1 (DEL1; also known as EGF-like repeat and discoidin I-like domain-containing protein 3), which was shown to inhibit initiation of periodontal inflammation and to promote its resolution [144][145][146][147] , may also regulate central inflammatory processes via its function to modulate demand-adapted myelopoiesis in the bone marrow 148 .…”
Section: Wwwnaturecom/nrimentioning
confidence: 99%
“…These interactions bridge apoptotic cells to macrophages and promote apoptotic cell phagocytosis (efferocytosis) and inflammation resolution (21). Consistent with these homeostatic functions, DEL-1 protects against inflammatory disorders in preclinical mouse or non-human primate models, including inflammatory bone loss in periodontitis, experimental autoimmune encephalomyelitis, pulmonary inflammation and fibrosis, and allergic asthma (16,18,20,(24)(25)(26).…”
Section: Introductionmentioning
confidence: 82%
“…As alluded to above, the anti-leukocyte recruitment function of DEL-1 depends on its interaction with the LFA-1 integrin (15,16). By interacting with avb3 integrin on different cell targets, DEL-1 regulates myelopoiesis (51), efferocytosis (21,23), osteogenic differentiation of progenitors (22), and regulatory T cell stability and function (24); and by binding αvβ6 integrin, DEL-1 regulates integrin-mediated activation of TGF-β (52). In this study, we showed that the interaction of DEL- Our findings are consistent with earlier reports that LFA-1 is required for optimal APCdependent T cell activation and induction of Ab responses in mice and humans (54,55).…”
Section: Discussionmentioning
confidence: 99%
“…Its efficacy has been tested in IL-17mediated inflammatory bone loss in mice and primates, as well as in a mouse model of multiple sclerosis (28,33,34). Besides leukocyte recruitment, DEL-1 exerts its immunomodulatory actions via resolution of inflammation by efferocytosis and induction of anti-inflammatory Treg response (35,36). The anti-recruitment action of DEL-1 is mediated via inhibition of β2-integrin/ICAM interaction, whereas efferocytosis and induction of Treg response are mediated via interaction of DEL-1 to αvβ3-integrin by its RGD sequence in the second EGF-repeat (29,37).…”
Section: Introductionmentioning
confidence: 99%